Severe hypokalemia mimicking classical electrocardiographic pattern of left Main coronary artery disease: A case report and a focused review of the literature - Vásquez Lozano Sergio Humberto; Porras Bueno Cristian Orlando; Ruiz Hernández Gabriel Fernando; Olarte Jurado Mabel Lucero; Maria Paula Blanco Rueda (Clinical Case Reports)
Key Clinical Message Several electrocardiographic alterations due to hypokalemia have been described, but the electrocardiographic presentation meeting criteria for occlusion of the left main coronary artery is very rare. We describe a case of hypokalemia simulating it.